Commissioning of a gas monitor detector for an undulator beamline in the VUV and EUV wavelength range. Issue 1 (1st December 2022) - Kirschner, Hans; Kaser, Hendrik; Gottwald, Alexander
Abstract: A gas detector system was implemented to monitor the absolute photon flux at the insertion device beamline of the Metrology Light Source. This system should overcome the drawbacks in the use of traceably calibrated semiconductor photodiodes, which are prone to radiation-induced degradation and not qualified for permanent real-time monitoring during the measurements at the beamline endstation. Gas monitor detectors are based on atomic photoionization. They do not suffer from radiation-induced degradation, and their transparency makes them suitable for real-time monitoring of the photon flux. We calibrated and commissioned such a monitor at the insertion device beamline in the vacuum- and extreme ultraviolet spectral range from 14 eV to 111 eV photon energy. The resulting photon flux measurement was compared to measurements made with a photodiode and shows deviations below 5 %, which agrees well with the calculated relative uncertainty of 4.7 %.